Notes for a Feathered Dawn: Eyes, Balaclavas and Hearts in Lemebel's “Deleuzian” Readings - María del Pilar Jarpa Manzur (Catedral Tomada: Revista de Crítica Literaria Latinoamericana, 2022)
From a critical gender perspective, this article offers an analysis of the chronicle that Pedro Lemebel dedicates to Subcomandante Marcos, paying special attention to the Deleuzian dimensions that it incorporates. Dimensions that are not only present in what could be interpreted as a theoretical wink, but also in the practices -visual, oral, written- with which Lemebel seems to overflow and enrich his philosophical origin. If, in general, within the multiple recreations of becoming that are promoted in his chronicles, Lemebel tends to question the symbolic universe of the new man, the text that consecrates Subcomandante Marcos seems to introduce unusual forms of subversion that question and at the same time confront the local revolutionary imaginary. However, it is not only a matter of destabilizing the binarized discourses of the revolution, but also of making visible other possible forms of disrespect and resistance. And that is what seems to be re-created in the memoirs that, in the context of the Chilean revolt of 2019, have taken Lemebel's name from the line of flight to the front line of fire.